Computer Views - Freud, Robert; Hahne, Harry; Dugdale, Antony; Hayes, Richard P. (Arc: The Journal of the School of Religious Studies, 1994)
Computer Views: UniVerse for Windows: Unicode Word Processing by Robert Freud 103 PC Bible-Search Software for Scholarly Research by Harry Hahne 109 Transparent Language: Language Learning Made Easy by Antony Dugdale 127 Exploring the Internet: A Review and Commentary by Richard P. Hayes 131